Efficacy and safety of simultaneous treatment with two biologic medications in refractory Crohn's disease. Issue 11 (24th April 2020) - Yang, Edward; Panaccione, Nicola; Whitmire, Natalie; Dulai, Parambir S.; Vande Casteele, Niels; Singh, Siddharth; Boland, Brigid S.; Collins, Angelina; Sandborn, William J.; Panaccione, Remo; Battat, Robert
Summary: Background: Biologic therapies in patients with Crohn's disease often yield low clinical and endoscopic remission rates. After multiple failed therapies, combining two biologic therapies is possibly the sole medical alternative to recurrent surgery. However, data on this approach are limited. Aims: To assess the efficacy and safety of concomitant use of two biologic therapies in the largest cohort to date of refractory Crohn's disease patients. Methods: Data were extracted from Crohn's disease patients started on dual biologic therapy at two referral centres. Biologics utilised include infliximab, adalimumab, vedolizumab, ustekinumab, certolizumab and golimumab. The primary outcome was endoscopic improvement (>50% reduction in Simplified Endoscopic Score‐Crohn's disease [SES‐CD] or explicitly stated). Endoscopic remission (SES‐CD < 3 or stated), clinical response (Crohn's disease–patient‐reported outcome‐2 score [PRO2] reduced by 8), clinical remission (PRO2 < 8), and C‐reactive protein (CRP) were also assessed. Results: A total of 22 patients with 24 therapeutic trials of dual biologic therapy were identified. The majority of patients had prior surgical resections (91%), stricturing (59%) or penetrating (36%) phenotype, and perianal fistulas (50%). Median number of prior failed biologics was 4. Endoscopic improvement occurred in 43% of trials and 26% achieved endoscopic remission. Fifty per cent had clinical response and 41% achieved clinical remission. There were significant post‐treatment reductions in median SES‐CD (14.0 [12.0‐17.5] to 6.0 [2.5‐8.0], P  = 0.0005], PRO‐2 (24.1 [20.3‐27.0] to 13.4 [4.6‐21.8], P  = 0.002] and CRP (17.0 [11.0‐24.0] to 9.0 [4.0‐14.0], P  = 0.02). Presence of perianal fistulas decreased from 50% to 33%. Adverse events occurred in 13% of trials. Conclusion: Dual biologic therapy was associated with clinical, biomarker and endoscopic improvements in selected patients with refractory Crohn's disease who failed multiple biologics. Further studies are needed to validate this approach.